2020
DOI: 10.1155/2020/7056261
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adipose-Derived Stem Cells, Dermal Regenerative Templates, and Platelet-Rich Plasma in Tissue Engineering-Based Treatments of Chronic Skin Wounds

Abstract: The continuous improvements in the field of both regenerative medicine and tissue engineering have allowed the design of new and more efficacious strategies for the treatment of chronic or hard-to-heal skin wounds, which represent heavy burden, from a medical and economic point of view. These novel approaches are based on the usage of three key methodologies: stem cells, growth factors, and biomimetic scaffolds. These days, the adipose tissue can be considered the main source of multipotent mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 186 publications
(206 reference statements)
0
21
0
Order By: Relevance
“…When activated by factors such as thrombin or calcium, alpha granules of the platelets could release various growth factors and cytokines such as platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), fibroblast growth factor-2 (FGF-2), and epidermal growth factor (EGF) [12,13]. The use of PRP has been described for a wide variety of clinical applications, particularly in craniomaxillofacial surgery, spine and joint arthroplasty, periodontal surgery, and wound healing [14][15][16][17][18]. Previous studies have demonstrated positive effects of PRP, supporting its clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…When activated by factors such as thrombin or calcium, alpha granules of the platelets could release various growth factors and cytokines such as platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), fibroblast growth factor-2 (FGF-2), and epidermal growth factor (EGF) [12,13]. The use of PRP has been described for a wide variety of clinical applications, particularly in craniomaxillofacial surgery, spine and joint arthroplasty, periodontal surgery, and wound healing [14][15][16][17][18]. Previous studies have demonstrated positive effects of PRP, supporting its clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the above-mentioned biomaterials have been shown to also improve the performance of multiple stem cell types in skin repair, including bone marrow-derived MSCs and epidermal stem cells [41,42]. Perhaps the combination currently most widely explored in clinical practice is the use of adipose tissue-derived stem cells with PRP [43][44][45][46][47][48]. As the nature (e.g., acute or chronic), severity (e.g., due to the presence of underlying disease), and location of wounds (e.g., in a region that requires hair regrowth) can be very diverse, the development of a broad variety of specialized tissue-engineering enhanced cell-based treatments (e.g., the use of adipose tissue-derived follicle stem cells for hair regrowth [49]) is a promising step in wound management and skin regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific progress in the laboratory with regenerative stem cells, growth factors, and biomimetic scaffolds is translating into clinical applications. 1 Peri-wound injection of fat has been used successfully to hasten healing in difficult wounds with or without negative pressure wound therapy (NPWT). 2 Tissue regeneration templates can cover but small areas of bone exposure; cost, availability, lack of insurance coverage, and difficulties with vascularization are significant downsides.…”
Section: Introductionmentioning
confidence: 99%